Role of Human Organic Cation Transporter 1 (hOCT1) Polymorphisms in Lamivudine (3TC) Uptake and Drug-Drug Interactions - Arimany-Nardi, Cristina; Minuesa, Gerard; Keller, Thorsten; Erkizia, Itziar; Koepsell, Hermann; Martinez-Picado, Javier; Pastor-Anglada, Marçal (Frontiers in Pharmacology, 2016)
Lamivudine (3TC), a drug used in the treatment of HIV infection, needs to cross the plasma membrane to exert its therapeutic action. Human Organic cation transporter 1 (hOCT1), encoded by the SLC22A1 gene, is the transporter responsible for its uptake into target cells. As SLC22A1 is a highly polymorphic gene, the aim of this study was to determine how SNPs in the OCT1-encoding gene affected 3TC internalisation and its interaction with other co-administered drugs. HEK293 cells stably transfected with either the wild type form or the polymorphic variants of hOCT1 were used to perform kinetic and drug-drug interaction studies. Protein co-immunoprecipitation was used to assess the impact of selected polymorphic cysteines on the oligomerization of the transporter. Results showed that 3TC transport efficiency was reduced in all polymorphic variants tested (R61C, C88R, S189L, M420del and G465R). This was not caused by lack of oligomerization in case of variants located at the transporter extracellular loop (R61C and C88R). Drug-drug interaction measurements showed that co-administered drugs (abacavir (ABC), zidovudine (AZT), emtricitabine (FTC), tenofovir diproxil fumarate (TDF), efavirenz (EFV) and raltegravir (RAL)), differently inhibited 3TC uptake depending upon the polymorphic variant analysed. These data highlight the need for accurate analysis of drug transporter polymorphic variants of clinical relevance, because polymorphisms can impact on substrate (3TC) translocation but even more importantly they can differentially affect drug-drug interactions at the transporter level.